2017
DOI: 10.3390/atmos8120240
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Raindrop Size Distribution on Throughfall Dynamics under Pine and Birch Trees at the Rainfall Event Level

Abstract: Abstract:Part of precipitation is intercepted by forest canopies, while the rest reaches the ground as throughfall or stemflow. This process is influenced by various meteorological variables, of which we have mainly focused on drop diameter and velocity. Rainfall in the open and throughfall under birch and pine trees have both been measured since 2014 in Ljubljana, Slovenia. The results demonstrate that the total throughfall during 3.5 years was 73% and 53% of rainfall under birch and pine trees, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 46 publications
4
23
0
3
Order By: Relevance
“…An analysis of factors that affect the S and wettability is of increasing interest to ecohydrologists [8,29,[50][51][52][53]. However, the mechanism of the adherence of water to the plant material is not yet fully understood [8,9,54].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of factors that affect the S and wettability is of increasing interest to ecohydrologists [8,29,[50][51][52][53]. However, the mechanism of the adherence of water to the plant material is not yet fully understood [8,9,54].…”
Section: Discussionmentioning
confidence: 99%
“…Under dry conditions, interception rates are primarily controlled by rainfall intensity [14]. Although rainfall characteristics were considered to be the most influential variables, the number of raindrops, raindrop diameter, and velocity were hardly included in the analyses of rainfall effects on canopy interception [15][16][17], except for in a study by Zabret et al [17], who reported that raindrops with a larger diameter (6.5-8.5 mm) and higher velocity (7.6-10.4 ms −1 ) reduced canopy interception of rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Forest canopies intercept incident rainfall and thus change the rainfall distribution and its amount (Crockford & Richardson, ); consequently, their TF DSD differs from open precipitation (Hall & Calder, ). With the advent of optical disdrometers, a number of studies have begun to examine the effects of meteorological conditions, canopy structure, and the role of plant surfaces on TF DSD (e.g., Frasson & Krajewski, ; Hall & Calder, ; Nanko, Hotta, & Suzuki, ; Nanko, Hudson, & Levia, ; Nanko, Watanabe, Hotta, & Suzuki, ; Zabret, Rakovec, Mikoš, & Šraj, summarized in Levia et al, ). These studies investigated the following species: Zea mays L.(maize; Frasson & Krajewski, ), Pinus caribaea Morelet (Caribbean pine) , Eucalyptus camaldulensis D. (river red gum), and Tectona grandis L. F. (Teak; Hall & Calder, ) as well as Chamaecyparis obtusa (Siebold & Zucc.)…”
Section: Introductionmentioning
confidence: 99%